2018
DOI: 10.1016/j.cmi.2018.03.025
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Roche LightMix Gastro parasites multiplex PCR assay detecting Giardia duodenalis, Entamoeba histolytica, cryptosporidia, Dientamoeba fragilis, and Blastocystis hominis

Abstract: Objectives: Multiplex PCR assays offer highly sensitive and specific tools for the detection of enteric pathogens. This prospective study aimed at comparing the novel Roche LightMix Modular Assay Gastro Parasites (LMAGP) detecting Giardia duodenalis, Entamoeba histolytica, Cryptosporidium spp., Blastocystis hominis, and Dientamoeba fragilis with routine laboratory procedures. Methods: Stool specimens (n ¼ 1062 from 1009 patients) were consecutively examined by LMAGP, R-Biopharm Ridascreen enzyme immunoassays (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…In addition, these methods are more expensive than polymerase chain reaction (PCR), which is now accepted in most laboratories as the gold standard for the detection of this parasite in the stool. Previous studies have shown that compared to PCR, microscopy, ELISA, and immunochromatographic test (ICT) are less convenient in terms of cost, sensitivity, and specificity and also are more time consuming [54][55][56]. Although there have been important advances in diagnostic tools (i.e., the availability of multiplex PCR assays for the detection of intestinal protozoa), the accessibility to this molecular technique is limited in some labs and totally absent in others.…”
Section: Diagnosismentioning
confidence: 99%
“…In addition, these methods are more expensive than polymerase chain reaction (PCR), which is now accepted in most laboratories as the gold standard for the detection of this parasite in the stool. Previous studies have shown that compared to PCR, microscopy, ELISA, and immunochromatographic test (ICT) are less convenient in terms of cost, sensitivity, and specificity and also are more time consuming [54][55][56]. Although there have been important advances in diagnostic tools (i.e., the availability of multiplex PCR assays for the detection of intestinal protozoa), the accessibility to this molecular technique is limited in some labs and totally absent in others.…”
Section: Diagnosismentioning
confidence: 99%
“…The present study evaluated three commercial multiplex PCR assay analytical performances compared to a composite reference method based on microscopic examination and E. histolytica -specific adhesion detection on a well-defined stool samples collection. According to our findings, these assays offer a higher detection rate of gastrointestinal protists regardless of the considered panel [ 1 , 2 , 10 , 12 , 14 , 15 , 18 , 23 ], illustrated by an overall analytical sensitivity of 93.2% for G-DiaParaTrio, 96.5% for Allplex ® GI parasite and 89.6% for RIDA ® GENE compared to 59.6% for microscopic investigation [ 25 , 29 ]. These results should place molecular diagnosis as the first-line diagnosis for gastrointestinal parasites.…”
Section: Discussionmentioning
confidence: 96%
“…PCR-based molecular diagnostic techniques have obvious advantages in the accurate identification of intestinal protozoan species and detection of mixed infections of multiple intestinal protozoa. These techniques can compensate for the lack of sensitivity and high skill requirements of microscopic examination ( Friesen et al, 2018 ; Tsui et al, 2018 ; Jerez Puebla et al, 2020 ; Robinson et al, 2020 ; Shahbazi et al, 2020 ; Cai et al, 2021 ; Calle-Pacheco et al, 2022 ). In particular, the qPCR method does not require electrophoresis and the results can be analyzed directly using images and data such as amplification curves and Ct values, making it ideal for use in a variety of medical settings where specialist parasitological microscopy staff are scarce.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the quality of the microscopic examination is highly dependent on the skills of the laboratory technician ( Khare et al, 2014 ). There are several PCR-based methods that are used in the diagnosis of E. histolytica , G. lamblia , and C. parvum ( Friesen et al, 2018 ; Tsui et al, 2018 ; Jerez Puebla et al, 2020 ; Robinson et al, 2020 ; Shahbazi et al, 2020 ; Cai et al, 2021 ; Calle-Pacheco et al, 2022 ). Among the PCR methods developed for better diagnostics, real-time quantitative PCR (qPCR) methods are considered the leading ones as they are highly sensitive and specific.…”
Section: Introductionmentioning
confidence: 99%